Dropouts and its Reasons in a Community Campus: A Narrative Inquiry - Ghimire, Bholanath (Dhaulagiri Journal of Contemporary Issues, 2024)
This study has predominantly explored the primary challenges associated with the dropout rates in higher education institutions. Furthermore, this research paper seeks to analyze the dropout rates within bachelor's degree programs at Myagdi Multiple Campus (MMC) and delve into the underlying causes for these dropouts. Among the four primary factors contributing to the dropout rate under investigation in this study, the personal-related factor is identified as the most influential. It has explored a variety of the reasons of the dropout: the pursuit of foreign employment, not getting suitable job at homeland, low motivation rate for higher study and parental socio-economic status. Moreover, the objective of this study is to identify the reasons of the dropout in bachelor level fundamentally at a community campus, and attempt to recommend the positive feedbacks to the concerned authority for upliftment of the present situation. This study has employed interpretivism as the research paradigm, phenomenology as research design and narrative inquiry as research methodology. The theories that I have employed the dominant motivational theories in this study: Maslow’s Hierarchy of Needs and Tinto’s model. For the purpose, I have applied Google forms to collect forty participants' opinions through non-random judgement sampling and the phone calls for the interview with seven participants as the tools for collecting the required data for the designated study. Question included in form regarding student’s background and credentials, parents' education level, current educational status, occupation, income, specific reasons for dropping out, family support, satisfaction with MMC, and opinions on the duration of the bachelor's program. The implications of this study are to improve and boost up higher education policy for controlling and monitoring the existing dropout rate of the community campuses.